On the Determinants of Voluntary Disclosure by Indian Companies. (June 2015) - Charumathi, B.; Ramesh, Latha
In the current scenario of financial reporting regime, investors are increasingly looking at the disclosure practices of companies. The companies also face capital market pressures and need to disclose more than the regulatory norms. There could be several motivations for the companies to disclose more information voluntarily. This article explores the factors that determine the voluntary disclosure choices of the non-financial companies listed in the National Stock Exchange (NSE). The study uses a voluntary disclosure index (VDI) constructed by the authors with 81 financial and non-financial items across different categories such as strategy, forward looking, environment and social, etc. With the VDI, this study measures the voluntary disclosure levels for four financial years from 2009–2010 to 2012–2013 using the content analysis methodology. The study uses a panel data model to analyse the effects of three categories of variables, namely, firm characteristics, profitability and governance and found the fixed effect model to be suitable and leverage, size and institutional ownership emerged as the determinants of voluntary disclosures. The article is one of the first studies to use longitudinal data and a disclosure index specific to the Indian context.